Design Interactive Multimedia Based on Problem Solving Using Articulate Storyline on Dynamic Fluid Material - Ranti Addriani; Wahyuni Satria Dewi; Akmam; Putri Dwi Sundari (Postgraduate, University of Mataram, 2023)
This study aims to develop interactive multimedia based on problem solving using articulate storyline on fluid material in class XI Phase F. The research wants to test the validity and practicality of interactive multimedia using articulate storyline. The research method used R&D with Plomp’s model. Plomp's model consist of three phases, there are preliminary phase, prototyping phase, assesment phase. The subjects of this research were the physics lecturer of physics department, physics teacher and students in class XII IPA 9 MAN 2 Padang. The instruments used to collect data consisted of interview sheets with teacher, observation sheets, self-evalution questionnaire, expert review, one to one and small group questionnaire sheets. The data obtained were analyzed using validity index proposed by Aiken and practicality data using category interval. The result of this study show that the development of interactive multimedia using Articulate Storyline was valid with score 0.91, practical by students with score 95.25% and practical by teachers with score 95.83. Conclusion of this study explains that the interactive multimedia based on problem solving using articulate storyline is valid and practical toward learning process.